Analisis Kesalahan Siswa Berdasa Analisis Kesalahan Siswa Berdasarkan Objek Matematika dalam Menyelesaikan Soal Operasi Hitung Bilangan Bulat Kelas VII di SMP Negeri 99 Jakarta: Analisis Kesalahan, Objek Matematika, Operasi Hitung Bilangan Bulat, Kelas VII - Jesika Mariana Sinaga; Lukman El Hakim; Anny Sovia (Jurnal Riset Pendidikan Matematika Jakarta, 2025)
This study aims to determine the types of errors and the factors causing these errors by seventh-grade students at SMP Negeri 99 Jakarta when solving mathematics problems involving integer arithmetic operations. This study is a descriptive qualitative study. Data collection was conducted using tests and interviews. Written tests were conducted to identify students' errors based on Soedjadi's mathematical concepts, which are categorized into factual errors, conceptual errors, principle errors, and operational errors. Interviews were conducted to determine the cognitive aspects contributing to students' errors. Data analysis was conducted using a qualitative descriptive approach, consisting of several stages: data reduction, data presentation, and drawing conclusions. The results showed that conceptual errors were the most common errors made by students when solving arithmetic problems involving integers. The cognitive factors contributing to these errors were remembering (C1), understanding (C2), and applying (C3)